Explaining variability in therapist adherence and patient depressive symptom improvement: The role of therapist interpersonal skills and patient engagement. (27th September 2018) - Snippe, Evelien; Schroevers, Maya J.; Tovote, K. Annika; Sanderman, Robbert; Emmelkamp, Paul M.G.; Fleer, Joke
Abstract : Understanding why therapists deviate from a treatment manual is crucial to interpret the mixed findings on the adherence–outcome association. The current study aims to examine whether therapists' interpersonal behaviours and patients' active engagement predict treatment outcome and therapist adherence in cognitive behaviour therapy (CBT) and mindfulness‐based cognitive therapy (MBCT) for depressive symptoms. In addition, the study explores rater's explanations for therapist nonadherence at sessions in which therapist adherence was low. Study participants were 61 patients with diabetes and depressive symptoms who were randomized to either CBT or MBCT. Depressive symptoms were assessed by the Beck Depression Inventory‐II. Therapist adherence, therapist interpersonal skills (i.e., empathy, warmth, and involvement), patients' active engagement, and reasons for nonadherence were assessed by two independent raters (based on digital video recordings). Therapist adherence, therapists' interpersonal skills, and patients' active engagement did not predict posttreatment depressive symptom reduction. Patients' active engagement was positively associated with therapist adherence in CBT and in MBCT. This indicates that adherence may be hampered when patients are not actively engaged in treatment. Observed reasons for nonadherence mostly covered responses to patient's in‐session behaviour. The variety of reasons for therapist nonadherence might explain why therapist adherence was not associated with outcomes of CBT and MBCT.